'I enjoy learning': developing early years practitioners' identities as professionals and as professional learners. Issue 3 (27th May 2019) - Trodd, Lyn; Dickerson, Claire
Abstract: Emphasis on professionalisation of the childcare workforce internationally is associated with evidence that links education and experience of early years practitioners; quality of early education and care; and outcomes for children and families. In England, this has led to a proliferation of vocational undergraduate programmes. This article draws on research carried out with early years practitioners who were completing a sector endorsed foundation degree in early years programme that provided students in full-time employment with opportunities for professional and workplace learning. The students' views and experiences, documented in personal reflections and learning stories and voiced during focus groups, were complemented by those of early years managers and mentors. A critique of the findings to learn about developing early years practitioners' identities as professionals and as professional learners suggests that the students became confident, reflective professionals and learners who shared their learning and sought to implement change in their settings. This research has implications for developing early childhood education and care (ECEC) practitioners, new to academic study, as learners and as confident, reflective members of a professional workforce at a time of ongoing change and uncertainty in ECEC policy and practice nationally and internationally.